Bohemian-inspired jewelry : 50 designs using leather, ribbon, and cords - Eurto, Lorelei (Interweave Press, 2012)
"Bohemian-Inspired Jewelry showcases 50 beautiful designs that explore the rapidly growing trend of using cords and ribbon in jewelry. Inside this colorful instruction book are clear steps for incorporating these trendy materials into designs as well as troubleshooting tips for finishing the ends using the right findings and how to care for materials such as 100% silk ribbon. Bohemian-Inspired Jewelry is perfect for all levels of jewelry makers interested in creating beautiful, hip designs. Beginner jewelry artists will learn basic skills including, stringing, wire-wrapping, knotting, and braiding. Advanced designers are provided with a vast range of material and design ideas. Regardless of your skill level, you'll also learn how to feel confident with more complicated knotting. This is the perfect instructional book for jewelry designers interested in exploring the world of alternative materials in beaded jewelry. "--